Interactive Media Development of Procedures for Prayer (Tara Shalat) Based on Adobe Flash in Improving the Skills of Madrasah Ibtidaiyah Prayers - Cahyono, Guntur (Prodi PGMI IAIN Salatiga, 2019)
This research aims to develop interactive learning media for adobe flash-based prayer procedures/Tara (Tata Cara Shalat). Interactive media can develop prayer skills that are taught in the habituation process since the first grade of Madrasah Ibtidaiyah (MI). This research used development research (RD) methods. The development process in this study reached the stage of the formative evaluation process consisting of three steps, namely individual prototype material trials, small group trials, and field tryouts. This field trial involved subjects in a larger class, involving 15-30 (a whole class of learners) or larger groups, namely the available classes. The results of this field trial were used to make a product, material, or final design revisions. Interactive learning media can solve the problem of prayer skills regarding recitation and movement of prayer. Thus, interactive learning media made it easier for students to understand the procedures for prayer quickly; besides, the learning process will be more enjoyable